IDENTIFIKASI KOMPETENSI GURU SEBAGAI CERMINAN PROFESIONALISME TENAGA PENDIDIK DI KABUPATEN SUMEDANG - Fahdini, Reni; Mulyadi, Ence; Suhandani, Deni; Kartawinata, Julia (Mimbar Sekolah Dasar, 2014)
This study aims to explore the professional competence of elementary school teachers certified in Sumedang district. The study was conducted in the form of a survey in urban areas Sumedang district with a population of 592 elementary school teachers and 60 teachers certified as research samples. Total Respondents are 180 people consisting of 60 persons certified elementary school teachers, 60 peers who have not been certified, and 60 principals who captured data through questionnaires. Data were processedand analyzed with the rating scale measurement techniques and SPSS 16, and obtained the following results: 1) rating scale analysis results indicate that the professional competence of certified teachers in the Sumedang district, four aspects are in the ENOUGH category and one aspect is in the LESS category, and 2) the results of the attitude scale analysis using SPSS 16 shows that the professional competence of certified teachers in the Sumedang district are in GOOD category, but this condition isfar from the PROFESSIONAL category. Keywords: competence, professional, teacher, certificated, sumedang.Penelitian ini bertujuan untuk menelusuri kompetensi profesional guru-guru SD tersertifikasi di kabupaten Sumedang. Penelitian dilakukan dalam bentuk survei dengan populasi sebanyak 592 guru SD tersertifikasi dan 60 guru sebagai sampel penelitian yang berada pada kawasan perkotaan kabupaten Sumedang. Responden berjumlah 180 orang yang terdiri atas 60 orang guru SD tersertifikasi, 60 orang teman sejawat yang belum tersertifikasi, dan 60 orang kepala sekolah yang diambil datanya melalui angket. Data diolah dan dianalisis dengan teknik pengukuran rating scale dan program SPSS 16, dan didapatkan hasil sebagai berikut: 1) hasil analisis rating scale menunjukan bahwa kompetensi profesional guru tersertifikasi di kabupaten Sumedang, empat aspek berada pada kategori âCUKUPâ dan satu aspek berada pada kategori âKURANGâ, dan 2) hasil analisis skala sikap dengan menggunakan program SPSS 16 menunjukan bahwa pada umumnya guru tersertifikasi di kabupaten Sumedang tergolong pada kategori âBAIKâ, namun kondisi ini masih jauh dari kategori âPROFESIONALâ.